Religion and the American Presidency - Hallum, Anne Motley (A journal of church and state, 2013)
We encounter two underlying dilemmas for assessing religion and the American presidency in the fourteen essays in Religion and the American Presidency: first, the topic has been particularly subject to bias from scholars themselves. As the introductory chapter notes, “Much of what Americans read about religion and the US presidency is agenda driven.” The agenda may be to heighten the religiosity of US presidents, as in Michael Novak's book, On Two Wings: Humble Faith and Common Sense at the American Founding (2003), or perhaps more frequently, to ignore or downplay the influence of religion for most presidents. Therefore, when Jimmy Carter and George W.